Rab18 is not necessary for lipid droplet biogenesis or turnover in human mammary carcinoma cells - Jayson, Christina B. K. (Mol Biol Cell, 2018)
Rab GTPases recruit peripheral membrane proteins and can define organelle identity. Rab18 localizes to the endoplasmic reticulum (ER) but also to lipid droplets (LDs), where it has been implicated in effector protein recruitment and in defining LD identity. Here, we studied Rab18 localization and function in a human mammary carcinoma cell line. Rab18 localized to the ER and to LD membranes on LD induction, with the latter depending on the Rab18 activation state. In cells lacking Rab18, LDs were modestly reduced in size and numbers, but we found little evidence for Rab18 function in LD formation, LD turnover on cell starvation, or the targeting of several proteins to LDs. We conclude that Rab18 is not a general, necessary component of the protein machinery involved in LD biogenesis or turnover.